2001
DOI: 10.1182/blood.v97.6.1566
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome 13 abnormalities identified by FISH analysis and serum β2-microglobulin produce a powerful myeloma staging system for patients receiving high-dose therapy

Abstract: A careful prognostic evaluation of patients referred for high-dose therapy (HDT) is warranted to identify those who maximally benefit from HDT as well as those who clearly fail current HDT and are candidates for more innovative treatments. In a series of 110 patients with myeloma who received HDT as first-line therapy, times to event (disease progression and death) were studied through proportional hazard models, in relation to different prognostic factors, including a chromosome 13 fluorescence in situ hybrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
185
1
10

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 299 publications
(207 citation statements)
references
References 31 publications
11
185
1
10
Order By: Relevance
“…Based on their findings, we performed FISH analysis in a group of MM patients with the probes targeting at the similar loci as in Fonseca's study, and we were able to detect chromosomal abnormalities in CD138 ϩ -sorted cells in 72% of the tested MM patients compared with 24% by FISH evaluation performed on unsorted BM cells (P ϭ 0.0016). FISH on CD138 ϩ -sorted cells revealed the frequencies of individual genomic abnormalities in our study population similar to the frequencies observed in prior studies, such as 13q14 deletions in 44% compared with 30 to 54%, 4,6,12,27,28 the p53 deletion in 16.7% compared with 10 to 11%, 12,29 and IgH rearrangements in 44% compared with 50 to 60% in the literature. 30 -32 Of note, FISH on unsorted BM cells identified that the frequencies of individual genomic aberrations in our study series were all lower than those reported in the literature, further supporting FISH on untargeted cells as an inefficient approach for the identification of chromosomal abnormalities in MM.…”
Section: Discussionsupporting
confidence: 88%
“…Based on their findings, we performed FISH analysis in a group of MM patients with the probes targeting at the similar loci as in Fonseca's study, and we were able to detect chromosomal abnormalities in CD138 ϩ -sorted cells in 72% of the tested MM patients compared with 24% by FISH evaluation performed on unsorted BM cells (P ϭ 0.0016). FISH on CD138 ϩ -sorted cells revealed the frequencies of individual genomic abnormalities in our study population similar to the frequencies observed in prior studies, such as 13q14 deletions in 44% compared with 30 to 54%, 4,6,12,27,28 the p53 deletion in 16.7% compared with 10 to 11%, 12,29 and IgH rearrangements in 44% compared with 50 to 60% in the literature. 30 -32 Of note, FISH on unsorted BM cells identified that the frequencies of individual genomic aberrations in our study series were all lower than those reported in the literature, further supporting FISH on untargeted cells as an inefficient approach for the identification of chromosomal abnormalities in MM.…”
Section: Discussionsupporting
confidence: 88%
“…8 In these trials, analysis of prognostic factors indicated that bortezomib may be active in patients in whom other therapeutic approaches frequently fail. 7,9 This was particularly evident in the context of elevated serum b-2-microglobulin (b 2 -M) levels, generally considered as a factor of poor outcome after chemotherapy, [10][11][12] and in subsets of patients tested for abnormalities of chromosome 13q (Jagannath et al Proc ASCO 2005; 23: 560s; abstract). 9 Several groups have confirmed the negative impact of a chromosome 13q-deletion [del(13q14)] on outcome after standard-dose chemotherapy and high-dose therapy with autologous stem-cell transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11] Using metaphase analysis, D13 (predominantly monosomy, but sometimes interstitial deletion 12 ) is present in B50% of patients with abnormal karyotypes. Since this method frequently fails to detect the abnormal clone, D13 is seen in only 10-20% of patients overall compared to the 40-50% usually seen by interphase fluorescence in situ hybridization (iFISH) analysis.…”
Section: Introductionmentioning
confidence: 99%